Facilitating factors in the cross-cultural transfer of management practices: The case of a German multinational in Brazil. Issue 2 (April 2022) - Bausch, Madeleine; Barmeyer, Christoph; Mayrhofer, Ulrike
Highlights: This study focuses on management practices of a German multinational in Brazil. We find three ideal-typical stages that compose the management transfer process. We identify nine facilitating factors that play different roles during the process. A hybrid organizational culture favors mutual learning and successful transfer. Findings show how management practices can be implemented in multinationals. Abstract: The transfer of management practices in multinational companies has been discussed as a central topic in international business. Research has mainly focused on the challenges associated with transfer processes, but little is known about facilitating factors in cross-cultural transfer, even less in emerging markets. Based on a single case study of a German multinational in Brazil, we examine the transfer of quality management practices and map this process into three ideal-typical stages. We identify nine facilitating factors that play different roles during the three stages and highlight their support for the subsidiary's successful development. Our findings contribute to constructive approaches of cross-border transfer and show that the emergence of a hybrid organizational culture through mutual learning favors the transfer of management practices in multinationals.